HUBUNGAN PENGETAHUAN DENGAN KEHADIRAN DAN PENGETAHUAN DENGAN KORESPONDENSI MENURUT MEHDI HA’IRI YAZDI - Ma'rief, Muammar Iqbal (Al-Iqro', 2024)
Epistemology is one of the category of philosophy that explores the nature and origin of knowledge. The nuances of epistemological thought are influenced by the thinkers' backgrounds and the sources of their philosophical perspectives. One of the figure in Islamic Philosophy is Mehdi Ha’iri Yazdi. Mehdi, an Iranian philosopher from a Shia family, hails from a lineage of revered religious figures. Influenced by the illuminative thought and preceding Islamic philosophers such as Al Farabi, Ibn Sina, and Al Ghazali, Mehdi is renowned for his epistemological concept known as Ilmu Hudhuri, which translates to knowledge by presence. His reflections on knowledge by presence delve into the intersection of illuminative philosophy and the Islamic philosophical tradition. In his book "The Principles of Epistemology in Islamic Philosophy: Knowledge by Presence," Mehdi also addresses another form of knowledge, namely knowledge by correspondence. Employing qualitative research methods and literature review, this article aims to explore the relationship between these two forms of knowledge (knowledge by presence and knowledge by correspondence) and the extent to which illuminative relations play a role in their dynamics.